2019
DOI: 10.18048/2019.57.02.
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Fuel Injector Nozzle Geometry - Influence on Liquid Fuel Contraction Coefficient and Reynolds Number

Lino Kocijel,
Vedran Mrzljak,
Maida Čohodar Husić
et al.

Abstract: This paper investigates the influence of the fuel injector nozzle geometry on the liquid fuel contraction coefficient and Reynolds number. The main three fuel injector nozzle geometry parameters: nozzle diameter (d), nozzle length (l) and nozzle inlet radius (r) have a strong influence on the liquid fuel contraction coefficient and Reynolds number. The variation of the nozzle geometry variables at different liquid fuel pressures, temperatures and injection rates was analyzed. The liquid fuel contraction coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The cam geometry is not the only thing that affects optimal consumption of the two stroke marine engine, but it is one of significance [1,2]. Comprehensive research also takes into account other parameters, some of which are listed here, which relate to the optimal fuel consumption and reduction of NOx emissions, such as fuel injector nozzle performance [3,4]. The mathematical spray models of the fuel oil injector nozzle parameters and their validation studied in the literature under [5,6], were concluded that implemented models showed very good agreement with the experimental results with respect to their vapor penetration and the spray shape what is related to the NOx emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The cam geometry is not the only thing that affects optimal consumption of the two stroke marine engine, but it is one of significance [1,2]. Comprehensive research also takes into account other parameters, some of which are listed here, which relate to the optimal fuel consumption and reduction of NOx emissions, such as fuel injector nozzle performance [3,4]. The mathematical spray models of the fuel oil injector nozzle parameters and their validation studied in the literature under [5,6], were concluded that implemented models showed very good agreement with the experimental results with respect to their vapor penetration and the spray shape what is related to the NOx emissions.…”
Section: Introductionmentioning
confidence: 99%